Late-term fetuses with reduced umbilical vein blood flow volume: An under-recognized population at increased risk of growth restriction. (May 2022) - Stampalija, Tamara; Monasta, Lorenzo; Barbieri, Moira; Chiodo, Antonella; Quadrifoglio, Mariachiara; Fantasia, Ilaria; Bello, Leila Lo; Barresi, Valentina; Ottaviani, Chiara; Di Martino, Daniela Denis; Marangon, Eleonora; Travan, Laura; et al.
Abstract: Objectives: To investigate the umbilical vein and uterine arteries blood flow volume (UV-Q, UtA-Q) in late-term pregnancies. Study design: This was a prospective observational cohort study of singleton pregnancies ≥40 + 0 weeks in which UV-Q and UtA-Q, both absolute and normalized for estimated fetal weight (EFW) values, were evaluated in relation to AC drop of ≥20 percentiles from 20 weeks to term, Doppler signs of fetal cerebral blood flow redistribution and composite adverse perinatal outcome. The presence of neonatal hypoglycaemia and the need of formula milk supplementation were also examined. Results: The study population comprised 200 women. Fetuses with AC drop (n = 34) had a significantly lower UV-Q and UV-Q/EFW than fetuses without AC drop (n = 166): median UV-Q 184 ml/min (IQR 143–225) vs 233 ml/min (IQR 181–277), p = 0.0006; median UV-Q/EFW 55 ml/min/kg (IQR 42–66) vs 63 ml/min/kg (IQR 48–74), p = 0.03. Fetuses with cerebral blood flow redistribution (n = 48) had a significantly lower UV-Q and UV-Q/EFW than those without (n = 134): median UV-Q 210 ml/min (IQR 155–263) vs 236 ml/min (IQR 184–278), p = 0.04; median UV-Q/EFV 58 ml/min/kg (IQR 45–70) vs 65 ml/min/kg (IQR 50–76), p = 0.04. There was a significant moderate correlation between middle cerebral artery pulsatility index (MCA-PI) and UV-Q and UV-Q/EFW (Spearman Rho −0.20 and −0.20; p = 0.008 and p = 0.006). Conclusions: The umbilical vein blood flow volume might have a potential role to identify fetuses with stunted growth in late-term pregnancies.